Update in pre-eclampsia. - Chanprapaph P. (2014)
Pre-eclampsia, formerly called pregnancy-induced hypertension, refers to the new onset of hypertension (SBP > or = 140 mmHg or DBP > or = 90 mmHg) and proteinuria (> or = 0.3 g protein in a 24-hour urine specimen or 1+ on dipstick) after 20 weeks of gestation in a previously normotensive women. It is a life-threatening, multi-organ involvement disease and remains the leading cause of maternal death. Its clinical manifestations are the result of generalized vasospasm, activation of the coagulation system, and changes in several humoral and autoregulatory systems related to volume and blood pressure control. Pre-eclampsia is responsible for high perinatal mortality and morbidity rates, primarily due to early termination of pregnancy. Fetus growth restriction, oligohyrdramnios and non-reassuring fetal status are the consequences of chronic placental hypoperfusion. Pre-eclampsia does not appear to accelerate fetal maturation, as once believed. Delivery remains the definitive treatment of choice for pre-eclampsia and should be timely. Cesarean section is not necessary and reserved for the obstetrical indications only. The expectant management may be considered for women remote from term (< 32 to 34 weeks of gestation) with stable and uncomplicated severe disease. The supportive management such as blood pressure control, seizure prevention, and fetal well-being assessment are also important to ensure the satisfactory outcome. To date, no screening test has been proved to be reliable and cost-effective. The prevention of pre-eclampsia with antioxidant therapy (vitamin C, E) has shown promise, but large, randomized trials are needed. Although controversy exists, calcium supplementation has shown no benefit in large trials, and most evidence suggests little or no benefit for low-dose aspirin as prevention in women in the low-risk category.